Kebijakan Luar Negeri Inggris : Studi kasus Penjualan Senjata Inggris ke Arab Saudi - Paganio, Eugenius George; Windiani, Reni (Journal of International Relations, 2020)
The relationship between Britain and Saudi Arabia has been going on for a long period, where the cooperation is in the fields of economy, security, technology, or resources. One of Britain's cooperation with Saudi Arabia is the field of arms trade. However, this has become a problem lately because these weapons were used by Saudi Arabia to commit crimes against humanity and peace, particularly Saudi Arabia's involvement in the conflict in Yemen. The research objective is to find out the factors that influence British policy to continue selling weapons to Saudi Arabia using the concept of Foreign Policy Decision Making. The concept is collaborated with data using qualitative explanative research methodology. Researchers found that there are several factors that influence British foreign policy to continue selling weapons to Saudi Arabia. These factors are the political conditions in the UK in which there is the influence of Theresa May as prime minister and interest actors namely arms companies that maintain connections and relations with government. The second factor is the economic factor, where the British dependence on weapons projects. And the last factor is a political factor regarding the British agenda with the Gulf State.